Effect of an aerobic exercise program and a weight circuit program on the quality of life, dyspnea, and cardiorespiratory resistance in subjects with chronic pulmonary disease - Delgado Acosta, Henry (2007)
The objective of this study was to determinate the effect of an aerobic exercise program and a weight circuit program on the quality of life, dyspnea and cardiorespiratory resistance in subjects with Chronic Pulmonary Disease (CPD). Methodology: the rehabilitation program was conducted for eight weeks, including a pre-test and a post-test, one on-site supervised session per week and two home sessions with direct telephone communication. Instruments: the St. George Respiratory Questionnaire was used to measure quality of life, the Borg Scale to measure dyspnea, and the Six Minute Walk Test to measure cardiorespiratory resistance. Subjects: 38 patients previously diagnosed with CPD, 18 men and 20 women; 27 subjects with an obstructive pathology and 11 with a restrictive pathology, with an average age of 69.8 ± 9.34 years.  Subjects were randomly divided into two groups: one did aerobic exercises (22 subjects) and the other one did aerobic exercises and resistance training (16 subjects). Statistical Analysis: Four-Way ANOVA (2x2x2x2) for the variables sex, treatment, and pathology.  Results: significant differences were found between measurements of the following variables: dyspnea (pre-test: 7.18 ± 0.69 points and post-test: 4.89 ± 0.68 points) (F = 228.770; p < 0.05), quality of  life (pre-test: 59.68 ± 7.50 points and post-test 81.75 ± 7.33 points ) (F = 228.770; p < 0.05), cardiorespiratory resistance  (pre-test 384.95 ± 51.02 mts. and post-test 432 ± 37.41 mts.) (F: 59.9; p<0.01).  However, no differences were found in sex, activity program or disease (p>0.05), or any interaction between variables (p>0.05). Conclusion: aerobic and anaerobic exercises improve the degree of dyspnea, the quality of life, and the cardiorespiratory resistance in CPD patients.